Exploring the Potential of a Regional CoVE in Green Innovation: Insights from Skopje Region - Mila Velkovska; Radmil Polenakovikj; Valentina Gecevska; Bojan Jovanovski; Trajce Velkovski (Springer Proceedings in Business and Economics, Economic Recovery, Consolidation, and Sustainable Growth, 2024)
This paper focuses on green transition and explores the potential of regional Centre of Vocational Excellence in green innovation in the Skopje Region, North Macedonia. The study involves engagement of key stakeholders through roundtable workshops and a quantitative survey, the analysis of which is a basis for the CoVE strategy. The findings present the opinions and perspectives of key actors from the quadruple helix, emphasising the importance of collaboration and partnership between different stakeholders and the need to continually assess and update educational programmes to prepare learners for the constantly evolving trends in the labour market. The CoVE in green innovation was established in December 2021 and in the moment its portfolio of services and capacities are being built.
Keywords: CoVE, Green innovation, VET